Respon Perkecambahan Benih Kopi Arabika Coffea arabika L. Terhadap Pemberian Hormon GA3 - Lolo, Andarias; Jasmin, Rahmadi; Boling, Jefferson (PALLANGGA: Journal of Agriculture Science and Research, 2025)
This research was conducted in September – November 2022 in Tiroan Village, Bittuang subdistrict, Tana Toraja district. This research aims to determine the response of Arabica coffee germination to the administration of GA3 and to determine the concentration of GA3 which has a significant effect on Arabica coffee germination. The purpose of this research is to provide references and information for future researchers regarding the response of Arabica coffee seed germination to GA3 administration and to increase insight and serve as a guide for further research. This research used a randomized block design (RBD) with a GA3 concentration factor, with four treatments, namely G0= without GA3, G1= 10 ppm GA3, G2= 20 ppm GA3, and G3= 30 ppm GA3. Each experiment was repeated three times so that there were 12 sprout tubs, each sprout tub was filled with 10 seeds. The experimental results showed that GA3 treatment had a significant effect on the speed of sprouts and the number of leaves. The G3 treatment showed the best results in all experimental parameters except germination percentage. Penelitian ini dilakukan pada September – November 2022 di Desa Tiroan, kecamatan Bittuang, kabupaten Tana Toraja. Penelitian ini bertujuan untuk mengetahui respon perkecambhan kopi arabika terhadap pemberian GA3 dan untuk mengetahui konsentrasi GA3 yang berpengaruh signifikan terhadap perkecambahan kopi arabika. Kegunaan dari penelitian ini untuk memberikan referensi dan informasi bagi peneliti selanjutnya yang menyangkut tentang respon perkecambahan benih kopi arabika terhadap pemberian GA3 dan menambah wawasan serta dijadikan pedoman untuk penelitian selanjutnya. Penelitian ini meneggunakan rancangan acak kelompok (RAK) dengan faktor konsentrsi GA3, dengan empat perlakuan yaitu G0= tanpa GA3, G1= 10 ppm GA3, G2= 20 ppm GA3, dan G3= 30 ppm GA3. Setiap percobaan diulang sebanyak tiga kali sehingga terdapat 12 bak kecambah, pada setiap bak kecambah diisi dengan 10 benih. Hasil percobaan menunjukkan bahwa perlakuan GA3 berpengaruh nyata terhadap kecepatan kecambah dan jumlah daun. Perlakuan G3 menunjukkan hasil terbaik pada semua parameter percobaan kecuali pada persentase perkecambahan.